Can National Identity Ever Have "Fundamental Values"?. Issue 1 (May 2020) - Stronach, Ian; Hodkinson, Alan
This brief article acts as an introduction to this special edition on Fundamental British Values (FBV). From the outset, it is important to state that we as a group of contributors believe it is fundamental to value Britain and all of its peoples in different and differing ways to those espoused in the Government Prevent Agenda, FBV, and the "media's moral panics" about the terrorist within.